2008
DOI: 10.1080/08927010801958960
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and hygienic property modifications of stainless steel surfaces induced by conditioning with food and detergent

Abstract: The effect of repeated conditioning procedures (25 runs), consisting of soiling (milk and meat products) and cleaning steps, on the hygienic status, physico-chemical properties and surface chemical composition of stainless steel (SS) surfaces, was investigated. Five SSs differing in grade and finish were used. Both soiling and surface cleaning/conditioning procedures resulted in a similar increase in the surface contamination with carbon, while the changes in the basic component of the surface free energy depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…The type and the composition of food residue on foodprocessing equipment have been suggested to influence both the population levels of attached cells and their resistance to disinfectants (6,20,24,33,44). Moreover, in accordance with previous studies, attachment of L. monocytogenes was found to increase with increasing temperature (6,19,33,38).…”
Section: Discussionsupporting
confidence: 74%
“…The type and the composition of food residue on foodprocessing equipment have been suggested to influence both the population levels of attached cells and their resistance to disinfectants (6,20,24,33,44). Moreover, in accordance with previous studies, attachment of L. monocytogenes was found to increase with increasing temperature (6,19,33,38).…”
Section: Discussionsupporting
confidence: 74%
“…It has been shown that in food environments, the presence and the nature of conditioning molecules play a major role in the hygienic status of SS surfaces (Jullien et al 2008). In this study, physico-chemical measurements were carried out on soiled surfaces at an air/liquid/solid interface.…”
Section: Discussionmentioning
confidence: 99%
“…This is important since work by others has shown that results in relation to adhesion force tend to suggest that at least for hydrophobic bacteria, adhesion is greater on hydrophobic materials (Midelet and Carpentier, 2002;Boulange-Petermann et al, 2006;Jullien et al, 2008). Thus, it might be suggested that a change in surface wettability due to organic material retention may affect trends in initial cell attachment to a surface.…”
Section: The Condition Of the Surfaces Following 10× 20× And 30× Autmentioning
confidence: 94%